(untitled) (Polis (Santiago), 2022)
The year 2019 registered the largest social mobilization of the last thirty years in Chile. What factors led to the growth of electoral abstention and the increase in mobilizations around unsatisfied demands? We argue that the institutional framework caused and deepened the malaise. We identify those institutional arrangements and explain their mechanisms. Empirically, we first analyze participation/abstention levels and mobilization trends, associating them with the accumulation of discontent with the system. Second, we present the results of a survey taken at the epicenter of mobilizations at the end of 2019 to sustain that what led to the outbreak was not apathy but discontent. The poll suggests that the majority of the protesters had voted in previous elections and planned to do so in the future. By identifying the institutional roots of the outbreak, the work provides a rationale for the solution that was given to the conflict.